Creativity, Technology, and the Modern World: Artificial Intelligence (AI) - Mehrad, Aida; Mehrad, Anita (Journal of Social Studies (JSS), 2024)
In today's fast-paced world, many factors contribute to the progress and development of society. One of the most significant aspects that contribute to individual growth is creativity. Therefore, it is crucial to recognize the factors that encourage and stimulate creativity in individuals. Families and society should promote creativity as it provides a strong foundation for young people's social and personal lives and helps them succeed in their future endeavors. Several characteristics can help foster creativity in adolescents. These include recognizing successful individuals, emphasizing creativity, encouraging the early development of creativity, providing a cooperative platform for growth, and highlighting the importance of creativity. Failure to recognize creativity can harm young people's personal and social lives and lead them down an unfulfilling path. Thus, raising awareness about creativity and providing the conditions for its growth is vital. This study explores the role of technology, particularly Artificial Intelligence (AI), in fostering creativity in the modern world and its impact on society. With the continuous development of technology, it is essential in the modern world that parents and society consider providing a convenient atmosphere for learning and updating the new generation by offering correct patterns and accurate information.